Association of Type D personality with cognitive functioning in individuals with and without cardiovascular disease — The Gutenberg Health Study. (1st July 2016) - Unterrainer, J.; Michal, M.; Rahm, B.; Hadzibegovic, J.; Wild, P.S.; Schulz, A.; Münzel, T.; Blettner, M.; Lackner, K.; Pfeiffer, N.; Blankenberg, S.; Denollet, J.; et al.
Abstract: Objective: Distressed ('Type D') personality is associated with adverse health outcomes in patients with cardiovascular disease (CVD). While personality traits from the Five-Factor Model are related to cognitive functioning, neither Type D personality nor its underlying traits negative affectivity (NA) and social inhibition (SI) have been investigated regarding cognition. We therefore compared the predictive value of Type D classification and its subcomponents NA and SI on planning performance in individuals with and without CVD. Methods: Type D personality traits (DS14) were determined in a population-based sample of 4026 participants (including 549 with CVD) aged 40–80 years from the Gutenberg Health Study (GHS) and related to planning performance as assessed with the Tower of London task. Current depression and anxiety were controlled as state variables. Results: Type D personality status was negatively associated with planning performance in the CVD patient group only (p < 0.001) but had no impact in the non-CVD group (p = 0.40). In the overall sample, NA was negatively and SI positively associated with planning performance. No differential effect on planning between groups was found for depression and anxiety. Conclusion: While the subcomponents NA and SI in the population-based sample confirm and extend previous research on personality traits and cognition, Type D personality classification in combination with CVD emerged as a risk factor for decreased cognitive functioning, independent of depression and anxiety. These findings implicate the need to early focus on individual differences in cognitive functioning in patients with CVD.